Pop Art. - Lippard, Lucy R.; Alloway, Lawrence; Calas, Nicolas; Lippard, Lucy R.; Marmer, Nancy (London : Thames and Hudson, 1968)
Adami, Valerio ; Alvermann, Hans Peter ; Anon ; Apple, Billy ; Arman ; Artschwager, Richard ; Baj, Enrico ; Bengston, Billy Al ; Berlant, Anthony ; Berman, Wallace ; Blake, Peter ; Blosum, Verne ; Boshier, Derek ; Brecht, George ; Burckhardt, Rudolph ; Burton, Dennis ; Caulfield, Patrick ; De Chirico, Giorgio ; Christo ; Collins, Jess ; Copley, William ; Curnoe, Greg ; D'Arcangelo, Allan ; Davis, Stuart ; Dine, Jim ; Donaldson, Anthony ; Donarski, Ray ; Drexler, Rosalyn ; Dubuffet, Jean ; Duchamp, Marcel ; Durkee, Stephen ; Eller, Jim ; Fahlström, Öyvind ; Festa, Tano ; Flint, Armand ; Gaul, Winfred ; Gill, James ; Goode, Joe ; Goodman, Sam ; Grooms, Red ; Hamilton, Richard ; Hay, Alex ; Hedrick, Wally ; Hefferton, Phillip ; Hockney, David ; Holland, Von Dutch ; Indiana, Robert ; Jensen, Leo ; Johns, Jasper ; Jones, Allen ; Katz, Alex ; Kemnitz, Bernie ; Kent, William ; Kienholz, Edward ; King, William ; Kitaj, R.B. ; Klapheck, Konrad ; Krushenick, Nicholas ; Kuntz, Roger ; Kuriloff, Aaron ; Kusama Yayoi ; Laing, Gerald ; Leger, Fernand ; Lichtenstein, Roy ; Lindner, Richard ; Lueg, Konrad ; Man Ray ; Marisol, Escobar ; Mondino, Aldo ; Murphy, Gérald ; O'Dowd, Robert ; Oldenburg, Claes ; Paolozzi, Eduardo ; Pettibone, Richard ; Pezzo, Lucio Del ; Phillips, Peter ; Pistoletto, Michelangelo ; Ramos, Mel ; Rancillac, Bernard ; Rauschenberg, Robert ; Raysse, Martial ; Richter, Gerd ; Rivers, Larry ; Rosenquist, James ; Rotella, Mimmo ; Ruscha, Edward ; de Saint Phalle, Niki ; Saul, Peter ; Schwitters, Kurt ; Segal, George ; Smith, Richard ; Snow, Michael ; Spoerri, Daniel ; Strider, Marjorie ; Telemaque, Hervé ; Thiebaud, Wayne ; Thompson, Jon ; Tilson, Joe ; Urata, Sunao ; Warhol, Andy ; Watis, Robert ; Weber, Idelle ; Wesley, John ; Wesselmann, Tom ; etc.
Engels
boek